Performance Evaluation of Projects using Earned Value Concept - Siti Choiriyah; Dyah Listyaningsih; Felicia Nuciferani; Fahmi Ferdaus; Gerry Sigma Perdana; Ratih Sekartadji (Jurnal Teknologi dan Manajemen, 2024)
The construction project is one of the jobs that demands the final result to align with the planning, necessitating a check on the performance obtained during the project to address any deviations from the initial plan. The Earned Value method is one of the techniques that can be used to assess project performance based on cost and time. The objective of implementing an evaluation with the Earned Value method is to understand the project's performance based on value variances and performance indexes and to identify solutions as early as possible if the project is experiencing delays. Calculations using the Earned Value method are based on budgeted cost of work scheduled (BCWS), cost for work performed (BCWP), and actual cost of work performed (ACWP). The research results on the Gunung Anyar apartment project reveal that the project experienced a delay of 3 weeks from the initial plan and a cost overrun of IDR 21,863,495,000 from the budget of IDR 19,533,411,725 (-12%). From the evaluation, it is evident that the Earned Value method needs to be applied during the ongoing project, especially when facing delays, to find solutions as early as possible to overcome the issues and prevent further significant losses.